2019
DOI: 10.3892/mmr.2019.10488
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑671‑3p regulates the development of knee osteoarthritis by targeting TRAF3 in chondrocytes

Abstract: osteoarthritis (oa) is a degenerative joint disease characterized by articular cartilage degradation and joint inflammation. a previous study showed that microrna (mir)-671-3p is involved in the development of oa, however, its function and molecular target in chondrocytes during the pathogenesis of oa remain to be fully elucidated. in the present study, miR-671-3p was significantly downregulated in knee oa cartilage tissues compared with normal cartilage tissues. The expression levels of pro-inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For example, hsa-miR-671-3p was diminished by more than 2-fold in the blood serum EVs of PsA patients compared to the PsV group. Previously, it was shown that reduced levels of hsa-miR-671-3p in osteoarthritic knee cartilage led to increased inflammation and cartilage degradation [ 48 , 49 ]. It has also been shown that OA patients’ serum levels of hsa-miR-671-3p are reduced compared to controls [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, hsa-miR-671-3p was diminished by more than 2-fold in the blood serum EVs of PsA patients compared to the PsV group. Previously, it was shown that reduced levels of hsa-miR-671-3p in osteoarthritic knee cartilage led to increased inflammation and cartilage degradation [ 48 , 49 ]. It has also been shown that OA patients’ serum levels of hsa-miR-671-3p are reduced compared to controls [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-671, located at 7q36.1, serves as a suppressor or an oncogene in different tumors and plays a vital role in the biological process of many types of cancer, particularly in osteosarcoma ( 24 ), breast cancer ( 25 ), and non-small cell lung cancer ( 26 ). MiR-671 could directly target microfibril-associated glycoproteins ( 26 ), tripartite motif 14 ( 27 ), forkhead box protein P2 ( 28 ) and M1 ( 25 ), TNF receptor-associated factor 3 ( 29 ), and cyclin D2 ( 30 ), involved in the proliferation, migration, and invasion of tumor cells. Besides, miR-671 may also regulate the PI3k/Akt signaling ( 31 ) and the Wnt signaling pathways ( 32 ) that are closely related to the occurrence and development of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that miR-671 is closely related to OA. Through miRNA sequencing analysis of tissues, plasma, and chondrocytes of OA patients, the results showed that miR-671-3p level was down-regulated during the rapid progression of the disease ( 36 ), and the expression of the downstream target gene, TNF receptor-associated factor, was enhanced ( 37 ). In the late stage of the disease, the increase of miR-671 can reduce the inhibition of cell proliferation and apoptotic stimulation induced by IL-1β and reduce the expression of type II collagen in chondrocytes, which can reduce the progression of OA ( 38 ).…”
Section: Mir-671 In Bone-related Inflammatory Diseasesmentioning
confidence: 99%